Residual properties of concrete exposed to elevated temperatures. Issue 3 (13th March 2019) - Rafi, Muhammad Masood; Aziz, Tariq; Lodi, Sarosh Hashmat
Abstract : The elevated temperature behaviours of concrete specimens made of three different concrete grades are presented in this paper. Cylindrical specimens of concrete mixes with 17 MPa (designated as M17), 21 MPa (designated as M21) and 27 MPa (designated as M27) target strengths were employed. Different temperature progression in the core of the concrete cylinders was observed for specimens of different concrete grades. Concrete discoloration started at 300°C, while hairline cracks appeared at 400°C on the surface of the cylinders. Pore pressure generated by steam and carbon dioxide during heating of the cylinders caused explosive spalling at a furnace temperature of 400–600°C. Similar loss of compressive strength of concrete was found for all the employed mixes, which reached to nearly 70% at 800°C. The ultimate strain of concrete increased at higher temperatures. The loss of concrete elastic modulus reached 80%, whereas nearly 50% tensile strength was lost at 600°C. A comparison of observed data with the theoretical predictions based on the analytical models suggested by some of the international codes was made and differences between the predicted and observed data were found. Coefficients of strength reduction and corresponding strains were proposed, which correlated well with the observed stress–strain curves.